2017
DOI: 10.1097/psy.0000000000000488
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Survival in a 17-Year Longitudinal Study of People With HIV: Moderating Effects of Race and Education

Abstract: Depression is associated with worse long-term survival in people with HIV during 17 years of follow-up. Interventions targeting depression may improve well-being and potentially survival in individuals with HIV. However, since depression did not predict survival in African Americans or those with low education, more research is needed to identify risk factors for long term outcomes in these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…These factors fall into the domains of sociodemographics, neighborhood and local environmental factors, social structures, individual biology, and intersecting societal stigmas. Structural factors, including poverty, low education, unstable housing, and food insecurity, contribute to increased vulnerability to HIV infection and poor HIV health outcomes [56,57]. Neighborhood and environmental factors, including violence and lack of safety, lack of adequate safe and steady water supply, wars, and natural disasters, cause psychological trauma, disrupt the delivery of medical supplies, and present barriers to healthcare access [5860].…”
Section: Intersecting Vulnerabilitiesmentioning
confidence: 99%
“…These factors fall into the domains of sociodemographics, neighborhood and local environmental factors, social structures, individual biology, and intersecting societal stigmas. Structural factors, including poverty, low education, unstable housing, and food insecurity, contribute to increased vulnerability to HIV infection and poor HIV health outcomes [56,57]. Neighborhood and environmental factors, including violence and lack of safety, lack of adequate safe and steady water supply, wars, and natural disasters, cause psychological trauma, disrupt the delivery of medical supplies, and present barriers to healthcare access [5860].…”
Section: Intersecting Vulnerabilitiesmentioning
confidence: 99%
“…Taken together, research to date has consistently identified pathways of both HIV-related stigma and life stress to important disease-related variables such as substance use, depression, and health outcomes in PLWHA. The associations to depression and substance abuse are also important in and of themselves because both depression [24,33,34] and substance use [35][36][37] have been associated with worse HIV outcomes over and above the effects of antiretroviral use or adherence. Studies to date have not fully examined the degree to which these constructs may be associated within one model, which may reveal a more nuanced understanding of how HIV-related stigma and life stress affect functional health in PLWHA.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this group might be targeted for the treatment of sleep disturbance for the prevention of depression. Efforts to decrease the prevalence of depression in HIV+, in turn, might improve adherence to HAART [ [29] , [30] , [31] ] and mitigate adverse medical outcomes [ 25 ] and mortality risk [ [32] , [33] , [34] , [35] , [36] ].Moreover, treatments that target insomnia complaints are thought to optimize the efficacy of depression prevention efforts, by reducing the number needed to treat to achieve benefit. Indeed, cognitive behavioral therapy for insomnia (CBT—I), as well as mindfulness based interventions (MBI), achieve >50% clinical response rate [ [37] , [38] , [39] ], suggesting that such prevention strategies are feasible in collaborative care (i.e., CBT—I) or community settings (i.e., MBI), with the potential to prevent incident depression in HIV+ MSM.…”
Section: Discussionmentioning
confidence: 99%